Efforts to Increase the Coverage of Child and Adolescent Health Screening during the COVID-19 Pandemic through Health Advocacy - Saputri, Endah Dwi; Marlina, Hastuti; Aznar, Aznar (Budapest International Research and Critics University, 2022)
Health screening of children and adolescents is carried out to prevent and overcome health problems as early as possible. This activity is an indicator of the health promotion program and community empowerment to achieve 100%. The coverage of screening for children and adolescents during the COVID-19 pandemic, the Pelalawan District Health Office, only reached 18.23%. The objectives are to identify problems, prioritize problems, look for alternative solutions to problems, and make an intervention plan (Plan of Action) by alternative solutions to increasing screening coverage for children and adolescents during the COVID-19 pandemic health advocacy. A qualitative method, with Rapid Assessment Procedures (RAP) approach. Informant retrieval technique using purposive sampling, namely the Head of Public Health, Head of Section, and Manager of Health Promotion and Community Empowerment Programs. Data analysis with in-depth interviews, document searches, and observations. The priority problem is the low coverage of screening children and adolescents during the COVID-19 pandemic. The most important alternative problem-solving is to do health advocacy to local governments and related SKPDs for screening during the COVID-19 pandemic. For efficiency and to reduce contact transmission, fill out a Google Form and do it door to door in areas where the internet network is complicated. The most important alternative problem-solving is to do health advocacy to local governments and related SKPDs for screening during the COVID-19 pandemic. For efficiency and to reduce contact transmission, fill out a Google Form and do it door to door in areas where the internet network is complicated. The most important alternative problem-solving is to do health advocacy to local governments and related SKPDs for screening during the COVID-19 pandemic, for efficiency, and to reduce contact transmission by filling out a Google Form and doing it door in areas where the internet network is complicated.